Structural attributes of firms, irreversibility, and uncertainty of corporate investment in Nigeria - Jonathan Oniovosa Ososuakpor (Investment Management & Financial Innovations, 2021)
In the Nigerian context, there is a gap in the literature on the structural attributes of firms and the extent to which corporate investments are irreversible. Thus, this study was to empirically examine the structural attributes of firms, irreversibility, and uncertainty of corporate investment using the real options theory of investment. The study is based on annual data series of firms listed on the Nigerian Stock Exchange from 2005 to 2019. The study measured structural attributes using competitiveness and monopoly/oligopoly of a firm, macroeconomic uncertainty, inflation, interest, and exchange rates, and examines their association with corporate investments. The study was conducted using a panel dataset adopting a fixed-effect estimation technique that takes into account potential endogeneity and firm specific-effects. The result showed that the macroeconomic uncertainty measure of exchange rate volatility is strongly detrimental to corporate investment decisions. Furthermore, interest rate and inflation volatilities are not detrimental to investment growth, while exchange rate uncertainty has a substantial negative influence on corporate investment. Besides, macroeconomic uncertainty was found to be a greater disincentive for firms with irreversible investments than for firms with more easily reversible investment projects.